Análise ecofisiológica e molecular em sementes de Genipa americana L. - Salla, Francesca (2015)
The tolerance to seed desiccation influences the capacity of the formation of soil seed bank and the survival of species in different environments, given that it is directly related to seed longevity. Thus, the objective of this work was to study the behavior of Genipa americana L. seeds in burial seed banks and the changes in antioxidant enzymes and proteins during seed drying at different rates. We installed an burial seed banks in the understory of a seasonal semideciduous forest in two distinct areas (hill top and riparian forest). We performed monthly evaluations of the germination and seedling emergence. To determine the protein profiles, heat resistant proteins and antioxidant enzyme activity in the physiological performance of the Genipa americana seeds, we subjected the seeds to two drying velocities (slow and fast). The results of the seed bank determined that Genipa americana seeds form a transitory seed bank, maintaining its viability only up to the fourth month after disposed in the natural environment. We observed effect of the drying rates over seed viability, in which the physiological quality of seeds submitted to slow drying was maintained. There was no effect of the drying rates and of the reduction of water content of the seeds over the electrophoretic pattern of total and heat resistant proteins. The decrease in tolerance to desiccation coincided with the reduction of the activity of enzymes catalase and superoxide dismutase, verifying the importance of these enzymes for the protection of seeds during drying.